Investigation of the energy spectrum and dose response of optical absorption bands in 4N single crystal LiF and LiF:Mg, Ti (TLD-100). (November 2017) - Biderman, S.; Druzhyna, S.; Reshes, G.; Eliyahu, I.; Oster, L.; Horowitz, Y.S.
Abstract: The optical absorption dose response of the 4.3 eV, 4.77 eV, 5.08 eV and 5.45 eV bands following gamma irradiation has been measured from 10 2 -10 5 Gy in 4N single crystal LiF and compared to the dose response of the same bands in LiF:Mg, Ti (TLD-100). The relative intensity of the 4.3 eV band in the 4N material is an order of magnitude lower than in TLD-100. In addition, its dose response enters into saturation above 10 4 Gy as opposed to the behavior of the dose response in TLD-100 which increases by over an order of magnitude between 10 4 and 10 6 Gy. The dose filling constant of the 4.3 eV band in 4N material can be fitted with a linear/exponentially saturating function with a value of β4N = 2.9 × 10 −4 Gy −1 . In TLD-100, on the other hand, the dose response requires two linear/exponentially saturating functions. The first is dominant at low dose with β1 = 1 × 10 −4 Gy −1 and the second is dominant at high dose with β2 = 1.1 × 10 −5 Gy −1 . The value of β2, approximately 26 times smaller than that of β 4N, suggests that the high dose behavior in TLD-100 does not result from the same "4.3 eV entity" in 4N material. Highlights: Comparison of the OA dose response of the main bands in 4N single crystal LiF and TLD-100. The dose behavior in TLD-100 is explained as a result of different "4.3 eV entity" in 4N material. The results support the correlation of the 4.3 eV band with the spatially correlated TC/LC.